ORGANIC SUBSTANCES IN SEDIMENT CORES FROM LUTZOW-HOLM BAY IN ANTARCTICA - マツモト, ゲンキ; ササキ, キヨタカ; ワタヌキ, クニヒコ; トリイ, テツヤ; MATSUMOTO, Genki I.; SASAKI, Kiyotaka; WATANUKI, Kunihiko; TORII, Tetsuya (National Institute of Polar Research, 1987)
P(論文) Total organic carbon (TOC), total nitrogen (TN), hydrocarbons and fatty acids in two recent marine sediment core samples from near the Langhovde Glacier (648m deep; Core-B, 117cm long) and from about 40km east of Core-B (778m deep; Core-A, 73cm long) in Lutzow-Holm Bay, Antarctica were studied to characterize the sources of organic substances and to elucidate the geochemical history of the studied sites. The sediment cores were composed mainly of glacial clay. The TOC contents of the sediment cores were considerably low, less than 2.1mgC/g of dry base. Unusually branched-C_<25 : 2> alkene was found as the most prominent hydrocarbon in both sediment cores, and it decreased largely with depth, reflecting probably unstable nature of this alkene for microbial degradation. This alkene is much likely to have been derived from ice algae. Normal saturated fatty acids ranging in carbon chain length from C_<10> to C_<32> were found in the samples, in addition to unsaturated and branched (iso-and anteiso-) components. The sources of these fatty acids are mainly plankton including ice algae and bacteria. Generally the contents of unsaturated fatty acids decrease with depth as in the case of the C_<25 : 2> alkene. The abundance of branched fatty acids in the Core-A sample reveals that bacterial contribution to this sample is considerably greater than that to the Core-B sample. Vertical profiles of the TOC, TN and fatty acids in the Core-B sample suggest that rework by glacial movements has taken place. departmental bulletin paper